Pathogenesis of Fibrosis: A Comprehensive Review of Oxidative, Inflammatory, and Immune Mechanisms Underlying Tissue Damage in Multiple Organ Systems - Taghreed Hazem Saber Al-fakje; Basma Salim Saad Allah AL- Hasso; Faehaa Azher AL-Mashhadani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Fibrosis, oxidative stress, inflammation, and immunity are tightly coupled processes leading to tissue damage and disease progression. Oxidative stress, triggered by reactive oxygen species (ROS), favors inflammation through the activation of pro-inflammatory cytokines as well as immune cells, especially macrophages. Chronic inflammation impedes the mechanisms of repair in tissues, resulting in an excess deposition of extracellular matrix (ECM) leading to fibrosis. Immune dysregulation mediated through T cells, B cells, as well as innate immunity also propels the fibrotic pathway. In contrast, fibrotic tissue reinforces oxidative stress and inflammation, forming a vicious cycle that sustains tissue injury and remodeling. Emerging evidence indicates that various molecular pathways are involved in this complex interplay. Key signaling cascades such as transforming growth factor-beta (TGF-β), nuclear factor-kappa B (NF-κB), and mitogen-activated protein kinases (MAPKs) play significant roles in amplifying oxidative and inflammatory responses. Dysregulation of antioxidant defense systems, including superoxide dismutase (SOD), catalase, and glutathione peroxidase, further aggravates oxidative stress and enhances tissue vulnerability. Moreover, metabolic alterations within immune cells contribute to the persistence of a pro-fibrotic environment. Activated macrophages, for instance, secrete profibrotic cytokines like interleukin-13 (IL-13) and tumor necrosis factor-alpha (TNF-α), while T helper 17 (Th17) cells promote chronic inflammation and tissue remodeling. This intricate cellular cross-talk highlights the importance of immune-metabolic regulation in fibrosis progression. Understanding these interconnected mechanisms offers promising therapeutic opportunities. Targeting oxidative stress with antioxidants, modulating immune responses with biologics, and inhibiting fibrogenic pathways using TGF-β or tyrosine kinase inhibitors are currently being explored in both preclinical and clinical settings. Such interventions hold potential for breaking the vicious cycle of oxidative stress, inflammation, and immunity, ultimately preventing irreversible organ damage and improving clinical outcomes in fibrotic diseases.